Modeling the Charging Choices of Battery Electric Vehicle Drivers by Using Stated Preference Data. Issue 1 (2016) - Wen, Yuan; MacKenzie, Don; Keith, David R.
The time, location, rate, and duration of plug-in electric vehicle (PEV) charging affects the performance of PEVs, including the amount of petroleum displaced, the emissions associated with electricity generation, the utilization of charging infrastructure, and the load placed on the electric grid. Empirical research has shown that charging preferences vary across PEV drivers and create large variations in the real-world utility factor for a fixed vehicle design. Nevertheless, most analyses of PEV usage rely on simple rule-based assumptions about charging behavior. In this paper, results from a web-based stated preference study of U.S. battery electric vehicle owners are displayed. Subjects were presented with situations representing potential charging opportunities and asked whether they would charge in such a situation. Binary, mixed, and latent class logit models of charging choices are investigated. The latent class logit fits the data best and allows identification of three basic types of decision maker: those who decide to charge on the basis of price and necessity; those who generally charge whenever they have the opportunity; and those who consider a wider range of factors, including charging power, dwell time, and the effect on their home charging bill. A majority of respondents are estimated to be willing to pay a premium of 2.35/h for Level 2 charging and 7.85/h for fast charging beyond what they would pay for Level 1 charging.